The Determinants Of Profitability In Indonesia Plantation And Food Crop Companies 2020–2024 - Aulia Puspita; Purwanto Purwanto (Jurnal Inovasi Bisnis dan Kewirausahaan, 2026)
This study analyzes the influence of debt-to-equity ratio, current ratio, inventory turnover, sales growth, and total asset turnover on return on assets in Indonesian plant and food crop companies. Using panel data regression with a fixed effects model, the study examined 21 plantation and food crop companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024, resulting in 99 observations after removing outliers. The result explains 66.93% of the variance in ROA, while the remaining 33.07% is explained by variables not included in the test. The results indicate that multiple factors influence the return on assets in the sample studied. The debt-to-equity ratio has a significant negative impact on the return on assets. The most important influencing factors, sales growth and total asset turnover, have a significant positive impact on return on assets, while the current ratio and inventory turnover have a minor or insignificant effect. Factories and investors in the plant and food crop sectors should use these correlations to assess their progress. This research contributes to the limited literature on financial determinants of profitability in the plantation and food crop sector, providing empirical evidence for stakeholders and investors in making financial decisions.